ISOLATION AND PURIFICATION OF THERMOSTABLE CHITINASE Bacillus licheniformis Strain HSA3-1a FROM SULILI HOT SPRINGS IN SOUTH SULAWESI, INDONESIA - HASNAH NATSIR; ABD. RAUF PATONG; MAGGY T. SUHARTONO; AHYAR AHMAD (International Journal of Pharma and Bio Sciences, 2013)
Thermostable chitinase is produced by B. licheniformis HSA3-1a from sulili hot springs in Pinrang, South Sulawesi which had been isolated and purified. Purification through ammonium sulphate precipitation step, dialysis, hydrophobic interaction chromatography with butyl sepharose FF matrix and gel filtration with sephadex G-75. The prepurification with ammonium sulphate precipitation results the highest chitinase activity on fraction 60-70% saturation. The results of hydrophobic interaction chromatography has two active fractions with highest activity on 40th and 43rd fractions, and the results of gel filtration chromatography to have an active fraction with the highest activity on 29th fraction. The results of purification were analyzed by SDS-PAGE showed a protein band at 97 kDa molecular weight estimates.